Brazil’s Two Africas, or which Africa to find in what Brazil? - Kier, Rune (Diálogos Latinoamericanos, 2008)
The article investigates the idea of Africa as central to the imagining of the Brazilian nation. It agues that the popular beliefs and the black movement differ significantly in their views of Brazil as well as the images of Africa they each use to explain the place of black people in the New World. Thereby the meaning of both Brazil and Africa are a matter of conflict depending on whether Brazil is seen to be a racial democracy or fraught with structural racism, and whether Africa is a place of famine, civil war and deceases having lost its past glory or in fact a glorious place of proud kings and queen. Each picture of Africa and Brazil connotes different positions for black Brazilians. The picture is further complicated by the Roots Tourism from North America recombining the elements from each to create a place of origin, an Africa in Brazil.